Upaya Peningkatan Hasil Belajar melalui Media Gambar pada Siswa SDN Karangjambu - Widia Astuti, Novita Adellia; Susanti, Tri Erna; Nurkhasanah, Wiji (Mozaic : Islam Nusantara, 2024)
The aims of this research are: (1) To find out to what extent image media can increase student activity in ablution material in class II of SDN Karangjambu Kebumen. (2) To find out to what extent image media can improve the learning outcomes of ablution material in class II students at SDN Karangjambu Kebumen. This research is classroom action research (PTK) which generally aims to improve student learning outcomes on ablution material in Islamic Religious Education (PAI) subjects. The results of this research show that: (1) there is an increase in student activity and learning outcomes in ablution material through image media in class II students at SDN Karangjambu Kebumen. Based on the recapitulation results in the pre-cycle, student activity was only 48.5% (not good), in cycle I it was 60% (fairly good), while in cycle II it reached 80% (very good). (2) The use of image media can improve the learning outcomes of ablution material for class II students. This can be seen from the increase in the completeness of student learning outcomes regarding ablution material in cycle I, 66%, increasing to 93% in cycle II. It can be concluded that through image media in the process of learning ablution material, it can increase the activity and learning outcomes of class II students at SDN Karangjambu Kebumen for the 2023/2024 academic year.